2020
DOI: 10.4162/nrp.2020.14.5.425
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vegetable oils with different fatty acid composition on high-fat diet-induced obesity and colon inflammation

Abstract: BACKGROUND/OBJECTIVES: Different fatty acids exert different health benefits. This study investigated the potential protective effects of perilla, olive, and safflower oils on high-fat diet-induced obesity and colon inflammation. MATERIALS/METHODS: Five-week old, C57BL/6J mice were assigned to 5 groups: low-fat diet (LFD), high-fat diet (HFD) and high-fat diet supplemented with-perilla oil (HPO), olive oil (HOO), and safflower oil (HSO). After 16 weeks of the experimental period, the mice were sacrificed, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…Surprisingly, the 100 and 500 mg/kg/day of PSO treatment significantly reduced dyslipidemia in HFD-fed rats, as displayed by the lowered TC, TG, and LDL levels but unaffected HDL levels. Other studies have shown that supplementation with PSO ameliorated HFD-induced dyslipidemia by suppressing lipogenesis and increasing lipid oxidation in the liver [17,40]. PSO also decreased serum cholesterol, and arterial and hepatic lipid aggregation by regulating lipogenesis and lipolysis pathways in HFD mice [16].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Surprisingly, the 100 and 500 mg/kg/day of PSO treatment significantly reduced dyslipidemia in HFD-fed rats, as displayed by the lowered TC, TG, and LDL levels but unaffected HDL levels. Other studies have shown that supplementation with PSO ameliorated HFD-induced dyslipidemia by suppressing lipogenesis and increasing lipid oxidation in the liver [17,40]. PSO also decreased serum cholesterol, and arterial and hepatic lipid aggregation by regulating lipogenesis and lipolysis pathways in HFD mice [16].…”
Section: Discussionmentioning
confidence: 90%
“…In the present study, we showed that PSO, which contains high amounts of PUFA, attenuated gut dysbiosis, intestinal barrier integrity disruption, intestinal inflammation, intestinal oxidative stress, systemic inflammation, and oxidative stress, and also decreased dyslipidemia and peripheral insulin resistance in HFD-fed rats. Similarly, long-term dietary supplementation with PSO ameliorated gut dysbiosis in HFD-induced colon inflammation by reducing the number of Enterobacteriaceae and elevating the number of Bifidobacteria, resulting in an increase in tight junction expression and a reduction in pro-inflammatory cytokine production [40]. Dietary supplementation with PSO for 16 weeks has shown lessened the HFD-induced nonalcoholic fatty liver disease and hepatic inflammation in an animal model [17].…”
Section: Discussionmentioning
confidence: 97%
“…Tissues were collected, frozen immediately, and stored at −72 °C, and some parts of the tissues were fixed in formalin for histological evaluation. After dissection of the colon, edema or ulceration level was recorded as previously reported [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…In a recent mouse study, a reversal of detrimental effects associated with high-fat diet was shown with the supplementation of three types of dietary oils, detectable as attenuation of the decrease of Bifidobacteria and suppression of the increase of the Enterobacteriaceae in the murine gut 17 . Notably, this particular study was culture-based rather than metagenomics-based.…”
Section: Introductionmentioning
confidence: 99%